Employment Experiences of Visible Minority Immigrant Women: A Literature Review - Sethi, Bharati; Williams, Allison (International Journal of Humanities and Social Science Research, 2015)
This literature review provides an overview of the employment experiences of visible minority immigrant women based on a critical review of the international English language peer-reviewed publications from 1980 to 2011.The overall goal of the review was to raise awareness and understanding of immigrant women’s employment experiences, health experiences, and the link between employment and health for this subpopulation. Approximately 126 papers articles were analysed. The key findings specific to women’s employment experiences are: 1) Economic welfare of immigrants continues to deteriorate with post-2000 arrivals to Canada facing much more occupational downward mobility than their 1990’s cohort; 2) Gender, ethnicity and immigrant status intersect to shape visible minority women’s employment experiences of deskilling, discrimination, and marginalization; 3) Collaboration is required with all three levels of government (federal, provincial, and municipal) employers, educational institutions, and community agencies to foster immigrant visible minority women’s economic integration in Canadian society.